Efficiency of photovoltaic technology for Citronella oil distillation - N., Safitri; Rihayat, T.; Suryani, Suryani; Riskina, S.; M. Jazuli, M. Jazuli; Siregar, J. P.; Jaafar, J.; T. Cionita, T. Cionita; Fitria, Fitria (2020)
Utilization of solar rays is currently very intensively carried out as renewable energy by utilizing endless energy due to its use, namely sunlight. Solar Cell or commonly called Photovoltaic system is a module that is used to absorb heat which is exposed to sunlight which is converted into electrical energy. The magnitude of the potential of sunlight that can be absorbed depends on the cell size and absorption of a solar cell against sunlight. In order to optimize the use of solar panels, a control system is needed that can control the position of the solar panel to always follow the direction and position of the sun automatically. Using modules (solar panels) with a capacity of 100 Wp can absorb heat converted to electricity as much as 100 watts/hour. This is a big advantage if it is able to be applied as a conventional electric substitute. In Southeast Asia in Aceh especially the sun shines from 09.00 a.m. until 15.00 a.m. this is a big advantage, by using a solar cell that has a capacity of 100 Wp for ± 5 hours a day when exposure to sunlight can produce power of 650 Watts/day. If the solar cell is used as many as 48 units of solar cells, then in a day can produce as much as 24,000 watts of electrical energy. This potential electrical energy can commonly use to facilitate the distillation of essential oils.